Efektifitas Model Pembelajaran Self-Organised Learning Environtment (Sole) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Desain Komunikasi Visual Kelas X SMKNegeri 2 Bone Faidah Yusuf - Jusman Jusman; Muh. Iskak (Jurnal Ilmiah Wahana Pendidikan, 2023)
The effectiveness of the self-organized learning environment (SOLE) learning model on student learning outcomes in the Visual Communication Design subject class X SMKN 2 BONE. Thesis of the Educational Technology Study Program, Muhammadiyah University of Bone. Guided by mentors Syarifnur and Jusman. This research aims to determine the effectiveness of the self-organized learning environment (SOLE) learning model on student learning outcomes in the Visual Communication Design subject class X SMKN 2 BONE. This research is quantitative research with a pre-experimental type of research with a one group pre-test and post-test design. The data processed is data on the population and sample of students, pre-test and post-test learning outcomes, documentation, using a sampling technique, namely purposive sampling with a sample of class X DKV 1 totaling 26 students. The results of the infreential analysis using normality and homogeneity tests were obtained from normal and homogeneous data results. Significance hypothesis testing using paired samples pretest posttest obtained from a low significance value of 0.05, namely 0.00 (Sigcount <0.05) shows significant effectiveness between before being given treatment and after being given treatment using pretest and posttest with data processing in the form of the SPSS application Version 23. Based on the research that has been conducted, it can be concluded that the use of the self-organized learning environment (SOLE) learning model for students' Visual Communication Design learning outcomes is effective in class X at SMK Negeri 2 Bone